ENHANCING EMPLOYEE PERFORMANCE: THE ROLE OF HARD SKILLS, MOTIVATION, AND CAREER DEVELOPMENT - Lisdewi Muliati; Dwi Putra Muhammad Dhiya Hibatullah (Dynamic Management Journal, 2026)
The coffee shop industry's rapid growth demands a strategic focus on human capital to achieve sustainable competitive advantage. This study investigates the influence of hard skills, intrinsic motivation, and career development on employee performance within Point Coffee Tangerang, addressing a critical need to understand performance determinants in the service sector. Employing a quantitative approach, this research sampled 93 respondents selected from the employee population. Primary data were collected through structured questionnaires and subsequently analyzed using descriptive and inferential statistical methods. The findings reveal that hard skills, intrinsic motivation, and career development each exert a positive and significant influence on employee performance, both partially and simultaneously. Collectively, these three factors account for a substantial portion of the variance in employee performance, underscoring their critical role as key performance drivers. This research contributes empirically to human resource management literature by validating a comprehensive model of performance determinants specifically within the Small and Medium Enterprise (SME) context of the food and beverage industry. The novelty of this study lies in its integrated examination of these three variables within a single analytical framework in an Indonesian coffee shop setting. Practically, the results offer actionable insights for management to strategically enhance workforce capability and motivation, thereby fostering improved organizational outcomes.